Adventureman, volume 2 ebook A fairy tale of new york. - Fraction, Matt (Adventureman, 2022)
WHERE HIS STORY ENDED...HER STORY BEGINS! Everyone knows the story of how ADVENTUREMAN, the greatest pulp hero of all time, ended in a heartbreaking CLIFFHANGER with our hero facing his very execution...now, learn the startling truth about how, 80 years after his seeming demise, single mother Claire and her Adventurefan son Tommy light the spark of RESURRECTION! Can these inheritors of the Adventureman legacy rise up to face down the evil that bested the original?